Ksantypa – dobra żona Sokratesa - Marchewka, Anna (Collectanea Philologica, 2018)
After the death of Socrates, anecdotes and distorted stories about the philosopher’s family life and the unbearable character of his wife, Xanthippe, circulated in the general quasi literary circle. These stories were willingly read in subsequent epochs. Eventually, they preserved the model of the hellcat wife in the shape of Xanthippe, to which we still eagerly refer to. But did Socrates’ wife really deserve such a bad opinion? Is it possible for such a rating to be given by the desultory information we owe to Plato (Phaed. 60a) and Xenophon (Mem. II 2, Conv. II 10)? When attempting to defend the Xanthippe, an important source turned out to be a letter from Pseudo-Xenophon (vel Pseudo-Aeschines), which allowed us to look at the philosopher’s wife as his pupil, leading life according to Socrates’ teachings and surrounded by the care of his friends (Epist. XXI, Hercher 1873: 624).